(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study investigates the impact of Shopee on customer engagement within micro-businesses located in Novaliches Bayan, Quezon City. Grounded in Youcheng Wang’s (2024) theory of customer engagement in e-commerce live streaming, the research focuses on three core engagement dimensions: observation-based, interaction-based, and action-based engagement. This study utilized a descriptive-quantitative design, surveying 15 micro-business owners or employees and 30 customers through purposive-quota sampling. Data were collected using a validated questionnaire to evaluate Shopee’s impact on customer engagement metrics. Findings showed that observation-based engagement (such as passive browsing) was the most influential, with mean scores between 3.26 and 4.00. Interaction-based engagement (including live chats and feedback responsiveness) and action-based engagement (such as purchases and reviews) were rated moderately, with means ranging from 2.51 to 3.25. Statistical tests—Z-tests, Kruskal-Wallis, and Mann-Whitney U—revealed no significant differences (p > 0.05) between the evaluations of micro-business owners/employees and customers, supporting the null hypotheses (H01, H02) that Shopee’s effect on engagement is consistent across respondent groups and business types. Among the challenges faced, 83% of businesses reported intense competition, 67% of customers expressed security concerns, and other issues included high shipping fees and cart abandonment due to complicated checkout procedures. Despite these obstacles, Shopee was recognized for its contribution to broadening market access and lowering operational expenses for micro-businesses. This study recommends a strategic approach to boost customer engagement by enhancing SEO and product visibility through focused keyword research and Shopee Ads; utilizing live streaming and chatbots to enable real-time interactions; introducing loyalty programs and automated follow-ups to minimize cart abandonment; and encouraging platform improvements such as lower commission fees and enhanced seller training. It highlights the need for micro-businesses to balance Shopee’s expansive reach with personalized retention strategies and greater transparency to build security and trust. Grounded in Wang’s framework, the findings emphasize the synergy of observational, interactive, and action-based engagement in creating customer value, offering actionable insights for micro-businesses aiming to optimize their e-commerce presence in a competitive digital landscape.